2020
DOI: 10.3390/ijerph17113821
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Fibroids Increase the Risk of Thyroid Cancer

Abstract: Objectives: The formation of uterine fibroids (UF) is potentially linked to the development of thyroid cancer through a common factor: female sex hormones. Methods: We conducted a nationwide population-based cohort study to determine whether Taiwanese women with UF have an increased risk of thyroid cancer. The data of both the UF and control groups were derived from the National Health Insurance Research Database (NHIRD) of Taiwan. Groups were matched by the year of UF diagnosis, age, income, urbanization leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 30 publications
2
10
0
Order By: Relevance
“…9 In an analysis using the national health insurance research database of Taiwan, like this study, Sun et al reported that uterine broids increased the risk of thyroid cancer. 6 Our ndings are consistent with the previous studies showing that patients with uterine broids had more benign thyroid diseases such as hypothyroidism and thyroid nodules.…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…9 In an analysis using the national health insurance research database of Taiwan, like this study, Sun et al reported that uterine broids increased the risk of thyroid cancer. 6 Our ndings are consistent with the previous studies showing that patients with uterine broids had more benign thyroid diseases such as hypothyroidism and thyroid nodules.…”
Section: Resultssupporting
confidence: 93%
“…Previous studies have evaluated the association between uterine broids and thyroid diseases [6][7][8][9] .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations